2015
DOI: 10.1002/pmj.21468
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Project Success and Project Efficiency

Abstract: Many researchers have suggested that meeting time, scope, and budget goals, sometimes called ‘project efficiency,’ is not the comprehensive measure of project success. Broader measures of success have been recommended; however, to date, nobody has determined empirically the relationship between efficiency and overall success or indeed shown whether efficiency is important at all to overall project success. Our aim in this article is to correct that omission. Through a survey of 1,386 projects we have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(215 citation statements)
references
References 17 publications
5
200
0
10
Order By: Relevance
“…Others research the effects of PM on project success demonstrating a significant and positive relationship [34]. Recently Serrador and Turner (2015) showed that project efficiency (meeting cost, time, and scope goals) correlates moderately strongly to the overall success of the project (meeting wider business and company goals defined by key stakeholders) [35]. Other researchers highlight that project success is best judged by the stakeholders, in particular by the the main sponsor [36].…”
Section: Project Successmentioning
confidence: 99%
“…Others research the effects of PM on project success demonstrating a significant and positive relationship [34]. Recently Serrador and Turner (2015) showed that project efficiency (meeting cost, time, and scope goals) correlates moderately strongly to the overall success of the project (meeting wider business and company goals defined by key stakeholders) [35]. Other researchers highlight that project success is best judged by the stakeholders, in particular by the the main sponsor [36].…”
Section: Project Successmentioning
confidence: 99%
“…Finally, functional project performance is predicted by the gain in teamwork team self‐­efficacy, but budget and time project performance are not predicted by gains in task work team self‐efficacy. This is interesting in light of recent research, which shows that being on time and within budget are not necessarily useful measures of project success (Serrador & Turner, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a direct relationship between project success and project efficiency as the latter contributes considerably to the former (Serrador & Turner 2015). Mir and Pinnington (2014) however, argue that more emphasis should be placed on the other dimensions as project efficiency is the least important.…”
Section: Two-dimensional View Of Project Successmentioning
confidence: 99%
“…Project success was initially determined based on the triple constraint of time, cost and quality (Ika 2009;Jugdev & Müller 2005;Todorović et al 2015). However, it was realised that this perception was incomplete and stakeholder views had to be included, as well as benefits realisation (Baccarini 1999;Chih & Zwikael 2015;Lappe & Spang 2014;Marnewick 2016;Serra & Kunc 2015;Serrador & Turner 2015;Wateridge 1998). The proliferation of project management led to the inception of various standards and methodologies such as PMBOK ® Guide, P2M, APMBOK ® , PRINCE2 and ISO 21500.…”
Section: Conceptualising a Multidimensional Model Of Information Commmentioning
confidence: 99%